2004
DOI: 10.1126/science.1092995
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Tropical Vegetation Response to Rapid Climate Changes

Abstract: Identifying leads and lags between high- and low-latitude abrupt climate shifts is needed to understand where and how such events were triggered. Vascular plant biomarkers preserved in Cariaco basin sediments reveal rapid vegetation changes in northern South America during the last deglaciation, 15,000 to 10,000 years ago. Comparing the biomarker records to climate proxies from the same sediment core provides a precise measure of the relative timing of changes in different regions. Abrupt deglacial climate shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(161 citation statements)
references
References 34 publications
7
152
0
2
Order By: Relevance
“…Drier conditions are also reported in the Bolivian cordillera (van't Veer et al, 2000) A reduction of 60 % of the Amazon discharge, as compared to the modern flow, is noticed from the Amazon fan sediments (Figure 5h, Maslin and Burns, 2000) and reduced precipitations in northern Amazonia (Peterson et al, 2000) accompanied by the development of a dry savanna are inferred from the Cariaco Trench (Haug et al, 2001;Hughen et al, 2004). Oppositely, the YD has been interpreted as more 2000).…”
Section: Regional Integration Within South American Recordsmentioning
confidence: 79%
“…Drier conditions are also reported in the Bolivian cordillera (van't Veer et al, 2000) A reduction of 60 % of the Amazon discharge, as compared to the modern flow, is noticed from the Amazon fan sediments (Figure 5h, Maslin and Burns, 2000) and reduced precipitations in northern Amazonia (Peterson et al, 2000) accompanied by the development of a dry savanna are inferred from the Cariaco Trench (Haug et al, 2001;Hughen et al, 2004). Oppositely, the YD has been interpreted as more 2000).…”
Section: Regional Integration Within South American Recordsmentioning
confidence: 79%
“…Over long periods, climate change can cause important changes in the geographic distribution and abundance of major land cover types and animal habitats (Melillo, 1999;Parmesan and Yohe, 2003;Thomas et al, 2004). Hughen et al (2004), for example, found a rapid shift between arid grassland and wet forest in the Cariaco region during deglacial high latitude North Atlantic climate oscillations. Meta-analysis conducted by Root et al (2003Root et al ( , 2005 has also revealed a discernible trend in the population of both animals and plants as a consequence of climate warming over the past century.…”
Section: Introductionmentioning
confidence: 99%
“…While the static vegetation layer used in the analysis may seem arbitrarily conservative, it is not an overly pessimistic assumption. First, vegetation lags to past and ongoing climate shifts have been shown in literature to be in the order of decades (Hughen, Eglinton, Xu, & Makou, 2004; Kitayama, Mueller‐Dombois, & Vitousek, 1995; Wu et al., 2015). Second, mature, structurally complex native forests at high elevations likely take decades to develop given the very slow growth of its dominant species, ‘ohi’a (Atkinson, 1970; Drake & Mueller‐Dombois, 1993).…”
Section: Discussionmentioning
confidence: 99%